Penilaian Jurnal internasional : An Analysis of the Effects on Application of Management Accounting Information Systems and Quality Management Accounting Information - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Penilaian Jurnal internasional : An Analysis of the Effects on Application of Management Accounting Information Systems and Quality Management Accounting Information